RAPID PLASTIC DEFORMATION EFFECT IN SINTERING PROCESS - Nurdin Effendi (website, 2009)
ABSTRACT PLASTIC DEFORMATION EFFECT IN SINTERING PROCESS. The synthesis of a new austenitic alloy, named A-1, has been carried out as a study material for a power-reactor heat exchanger. Powder metallurgy method was utilized in the alloys´ synthesis. The alloys elemental components are Fe, Ni, Cr, Si, Mn, C and Ti. Each of the alloying components was first determined in terms of weight-percentages, before actual weighing on the microbalance apparatus. The components were blended together in a special purpose ball-mill for 46 hours. The first samples are in the form of pellets of 25 grams each, obtained by compaction process using a die with a 2.0 cm internal diameter, at a pressure of 8000 psi. After pre-sintering at 1050oC for 24 hours, sintering was carried out at 1250 ºC for 6 hours, escorted by rapid plastic deformation treatment that was carried out by forging for every half hour. The microstructure observation shows that the grains form disorder pentagon or more fractional and the high crystal defect or disorder. The distribution observation of elemental were carried out twice by EPMA; the first is as sintering just half hour where the rapid plastic deformation treatment not been carried out yet and the second is at the six hours sintering in which the rapid plastic deformation treatments were carried out. Keywords: Plastic deformation, rapid and sintering. ABSTRAK PENGARUH DEFORMASI PLASTIS CEPAT DALAM PENYINTERAN. Telah dilakukan pembuatan bahan austenitik baru yang dinamakan dengan A-1 sebagai bahan studi untuk penukar panas reaktor daya (PLTN). Pembuatan bahan paduan ini dilakukan dengan teknik metallurgi serbuk. Komponen unsur-unsur paduannya adalah Fe, Ni, Cr, Si, Mn, C, dan Ti. Masing-masing komponen bahan ditentukan persen beratnya dan ditimbang. Campuran unsur-unsur tersebut diaduk dengan ball milling selama 46 jam. Masing-masing sampel awal yang dibuat berupa pelet bermassa 25 gram, diperoleh dengan kompaksi menggunakan die berukuran diameter dalam 2,5 cm, dengan tekanan kompaksi 8000 psi. Setelah diberi perlakuan presinter pada 1050 oC selama 24 jam, sampel disinter pada temperatur sekitar 1250 oC selama 6 jam disertai perlakuan deformasi plastis dengan penempaan yang dilakukan dalam setiap selang setengah jam. Pengamatan struktur mikro dengan mikroskop optik menunjukkan bahwa bentuk butir fasa umumnya berbentuk pecahan segi lima atau lebih yang tidak teratur, dan mengandung jumlah dissorder kristal yang tinggi. Pengamatan distribusi unsur dilakukan dua kali dengan EPMA, yaitu pada saat proses sinter baru berlangsung setengah jam saat belum diberi perlakuan deformasi plastis cepat dan pada kedua saat sinter berlangsug enam jam yang diberi perlakuan deformasi plastis cepat. Kata kunci: Deformasi plastis, cepat,and penyinteran